Dress syndrome induced by cefixime: A case report - SAXENA, VIDUSHI; Kidwai, Saim; Rehman , Abdul; Khan, Mohammad Ashraf (Indian Journal of Case Reports, 2026)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a severe, potentially life-threatening hypersensitivity reaction characterized by fever, rash, hematological abnormalities, and internal organ involvement. Although it is most commonly associated with antiepileptic and sulfonamide drugs, cephalosporin-induced DRESS remains rare and underreported. We describe a case of a 19-year-old male who developed DRESS syndrome following administration of Cefixime, a third-generation cephalosporin widely prescribed for bacterial infections.